Material Adaptation by the Teachers of Senior and Vocational High School inToraja Utara in Teaching English - Dan Mangoki (Teaching English as a Foreign Language Overseas Journal, 2019)
The objective of this research is to know the kinds of material adaptation that have done by the teacher of senior and vocational high school inToraja Utara in teaching English. The researcher employed the descriptive qualitative method with interview and documentation to obtain the data. The population of this research are the English teachers of Senior High School and Vocational High School in Rantepao District which is consists of thirty two (32) the English teacher. Since the population of the research is relative large in number, the researcher used purposive sampling method, which means that not all of the population were taken as respondents. The researcher choose 8 the English teacher as subject. The data obtained from interview, syllabus, lesson plan and textbooks. The researcher analyzed the data by using the Miles and Huberman technique.The result of the data analysis to showed that the kinds of material adaptation that have done by the teacher of senior and vocational high school inToraja Utara in teaching English, are adding content, addressing ommisions, modifying content, extending tasks and modifying tasks. Thus, by six kinds of adaptation only one that never used by the teacher that is reorganize content.